2021
DOI: 10.1016/j.ijfoodmicro.2020.109030
|View full text |Cite
|
Sign up to set email alerts
|

Description of the temporal dynamics in microbial community composition and beer chemistry in sour beer production via barrel ageing of finished beers

Abstract: Currently, there is a strong interest in barrel ageing of finished, conventionally fermented beers, as a novel way to produce sour beers with a rich and complex flavour profile. The production process, however, remains largely a process of trial and error, often resulting in profit losses and inconsistency in quality. To improve product quality and consistency, a better understanding of the interactions between microorganisms, wood and maturing beer is needed. The aim of this study was to describe the temporal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
80
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(84 citation statements)
references
References 44 publications
(40 reference statements)
3
80
0
Order By: Relevance
“…Different studies have successfully isolated and identified Enterobacteriaceae in spontaneously fermentated beers, whether American Coolship Ales, Belgian Lambics, or Wild Ales [7,9,15]. In such cases, these bacteria were highly abundant (>8% of ASVs) in six beer samples.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Different studies have successfully isolated and identified Enterobacteriaceae in spontaneously fermentated beers, whether American Coolship Ales, Belgian Lambics, or Wild Ales [7,9,15]. In such cases, these bacteria were highly abundant (>8% of ASVs) in six beer samples.…”
Section: Discussionmentioning
confidence: 99%
“…In such cases, these bacteria were highly abundant (>8% of ASVs) in six beer samples. Although they are responsible for off-flavor production and can be harmful to health through biogenic amine production [1,9], these bacteria are also linked to the production of specific flavors related to young Lambics, such as 2,3-butanediol, ethyl acetate, higher alcohols, acetic acid, lactic acid, succinic acid, and fatty acids [10,24].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This interest is directly related to the development of an artisanal beer market, which seeks to develop products with new and original aromatic notes. In the case of the Belgium lambic beer the participation of non-Saccharomyces (in particular Brettanomyces genus) is key in the maturation phase for the development of some typical notes of this type of beer (Bossaert et al, 2021;De Roos et al 2020). Other interesting applications are the generation of low-calorie beers, low alcohol beers and even non-alcoholic beers (Basso et al, 2016;Bellut et al, 2018;Capece et al, 2021;Holt et al, 2018;Michel et al, 2016).…”
Section: Importance Of Non-saccharomycesmentioning
confidence: 99%